(3fHPI dWjaI Yf EHf eGShjIs - (3CHh RcQjGA jhMfG Hf eGShjI GdHZOGOj,J (B243 (3g` s
(3ChdgG (B:s
(3CYde Cf NhGU GdedM GdSdjeGfi fGaY HEPf Gddg JYGdi ef LejY GdCeQGV hjfbi GdQWhHI hjMO GdHUQ s
(3BNQgG (B:s
(3jSJNQL Ogf LejY GdCOgGf ef GdCMLGQ heGTGcdg hef CbQ HGPjf GbQjhS , hef JaGUjd GdCOgGf hGdCQhGM s
(3eLehYI ef BQGFg heLQHGJg aj GdWH hGdCOhjIs
(3fbdJ ef CUd bOjes
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B192 s
Keywords: (3GdWHs